Ultralow Power Energy Harvesting Body Area Network Design: A Case Study. (27th October 2015) - Zheng, Chenyu; Kuhn, William B.; Natarajan, Balasubramaniam
Abstract : This paper presents an energy harvesting wireless sensor network (EHWSN) architecture designed for use within an astronaut's space suit. The contribution of this work spans both physical (PHY) layer energy harvesting transceiver design and low power medium access control (MAC) solutions. The architecture consists of a star topology with two types of transceiver nodes: a powered gateway radio (GR) node and multiple energy harvesting biosensor radio (BSR) nodes. To demonstrate the feasibility of an EHWSN at the PHY layer, a representative BSR node is implemented. The BSR node is powered by a thermal energy harvesting system (TEHS) which exploits the difference between the temperatures of a space suit's cooling garment and the astronaut's body. It is shown that, through appropriate control of the duty cycle in transmission and receiving modes, it is possible to operate with less than 1 mW generated by the TEHS. This requires ultralow duty cycle which complicates MAC layer design because a BSR node must sleep for more than 99.6% of overall operation time. The challenge for MAC layer design is the inability to predict when the BSR node awakens from sleep mode due to unpredictability of the harvested energy. Therefore, a new feasible MAC layer design, GRI- (gateway radio initialized-) MAC, is proposed and analyzed.